Learning from the past to build the future governance of groundwater use in agriculture. Issue 7 (17th November 2021) - Petit, Olivier; Dumont, Aurélien; Leyronas, Stéphanie; Ballin, Quentin; Bouarfa, Sami; Faysse, Nicolas; Kuper, Marcel; Molle, François; Alcazar, Charlotte; Durand, Emmanuel; Ghoudi, Ridha; Hubert, Aline; et al.
ABSTRACT: The use of groundwater is increasing worldwide, particularly in agriculture. This leads to pumping races (from which the poorest farmers are often excluded), environmental disasters and the degradation of groundwater quality. Based on discussions between scientists and operational experts in two workshops held in 2018 and 2020, this paper, after taking stock of the dynamics and motivations of groundwater use in agriculture, reviews the solutions most commonly proposed, in particular by public authorities, to regulate the access to and use of this resource and to limit its over-exploitation. These (often optimistic) solutions generally combine regulatory or economic instruments, or indirect measures linking water to other issues, and mechanisms based on the participation of all users. However, they rarely question the intensive agricultural systems driving groundwater demand and fail to recognize the multifunctional nature of groundwater. To overcome these hurdles, we draw up possible ways forward for policymakers and resource users to develop negotiated solutions.